Variability of repairable bicuspid aortic valve phenotypes: towards an anatomical and repair-oriented classification - de Kerchove, Laurent; Mastrobuoni, Stefano; Froede, Lennart; Tamer, Saadallah; Boodhwani, Munir; van Dyck, Michel; El Khoury, Gebrine; Schäfers, Hans-Joachim (European journal of cardio-thoracic surgery, 2019)
The bicuspid aortic valve (BAV) exists in a wide variety of valve phenotypes. The aim of this study was to assess the anatomical characteristics of the different phenotypes and develop a classification system to aid surgical repair. In 178 consecutive patients operated on for aortic insufficiency or aortic dilatation in 2 centres, 11 anatomical parameters of BAV were measured by echocardiography and intraoperatively. All BAV judged potentially repairable were included in the study. Commissural orientation correlated positively with fusion length (R2 = 0.6, P < 0.001) and negatively with non-functional commissure height (R2 = 0.45, P < 0.001). The cohort was divided into 3 groups according to their commissural orientation (type A: symmetrical, 160-180°, n = 73; type B: asymmetrical, 140-159°, n = 74; and type C: very asymmetrical, 120-139°, n = 31). The patterns of cusp fusion, annulus and aortic size were similar among the groups. Fusion length and the geometric height of the cusps decreased from type A to C; non-functional commissure height increased from type A to C (P < 0.05). Patient age increased from type A to type C. Isolated aortic dilatation was more frequent in type A, and severe aortic insufficiency was more frequent in types B and C (P < 0.05). Valve repair techniques and management of commissural orientation varied among the 3 groups (P < 0.05). Aortic valve replacement and residual aortic insufficiency after repair were more frequent in type C (P < 0.05). The BAV phenotypes follow a continuous spectrum that extends from symmetrical to very asymmetrical BAV. We describe the main anatomical parameters (including commissure orientation, length of fusion and non-functional commissure height) and their variation across this spectrum. We propose a new repair-oriented classification system based on those parameters that can be used to predict valve repair techniques. This classification needs further validation with regards to surgical techniques and long-term outcomes.